Proactive production activity control by online simulation. (9th January 2012) - Cardin, Olivier; Castagna, Pierre
In this paper, we present a new application of discrete–event simulation as a forecasting tool for the decision support of the production activity control of a complex manufacturing system. The specificity of such an application of simulation is the short term of the forecasts. This specificity implies that the initial state of the simulation takes into account the actual state of the system. The development on a real–size flexible manufacturing system shows the technical feasibility of the developed concepts and the potential benefits on the productivity of a single example.